INVESTIGATING THE WRITING QUALITY OF STUDENTS WITH DIFFERENT PROFICIENCY LEVELS IN INTERACTION-BASED PAIR WORKS - Styati, Erlik Widiyani; Rodliyah, Rojab Siti (Universitas Pendidikan Indonesia, 2021)
Pair work, an activity involving learners working together in pairs, has been widely used in language learning, especially in writing classes. Many studies have reported the effectiveness of this technique in improving students’ writing. However, there is limited research on how the factors like students’ proficiency and the level of interaction may affect the effectiveness of pair work. Proficiency and interaction between students are important in writing activities because when students are proficient and given a chance to interact, communicate and collaborate with others, they tend to produce a good writing as a result of their collaboration. This study, therefore, aims at investigating whether or not there is a significant difference in students’ writing (1) between the high proficient students engaging in the dominant-dominant pairs (H-DDP) and those engaging in the dominant-passive pairs (H-DPP), and (2) between the low proficient students engaging in the dominant-dominant pairs (L-DDP) and those engaging in the dominant-passive pairs (L-DPP). This experimental research involved forty-eight fourth semester students of an English Education Department in a private university in Madiun, East Java, Indonesia as participants. The data were obtained from the students’ writing test and analysed using independent t-test of SPSS 18.0 version. The results show that the high proficient students engaging in the dominant-dominant pairs (H-DDP) gained better score in the aspects of content (26.50 24.82), organization (19.71 19.09), vocabulary (15.36 14.09) and grammar (13.43 12.73) on argumentative essay than the high proficient students in the dominant-passive pairs (H-DPP). Meanwhile, the low proficient students engaging in DDP can write better in the aspects of organization, vocabulary and mechanics. It is also found that proficiency affects the students’ ability to work in pair and to actively contribute to the process of writing an argumentative essay. This implies that teachers should consider students’ proficiency and level of social interaction before assigning students into pairs in writing classes.